Chaotic mixing characteristics in static mixers with different axial twisted‐tape inserts. (29th July 2015) - Meng, Huibo; Song, Mingyuan; Yu, Yanfang; Wang, Feng; Wu, Jianhua
Abstract The distinction of chaotic advection and mixing of high‐viscosity fluids in tubes equipped with four different twisted tapes, including KSM, MSM, RSM, and SSM, were evaluated by Lagrangian simulation. ∼23 550 massless particle tracers marked by red and black colours were respectively released in the semicircle and concentric circles of the inlet cross‐section. Mixing performance was evaluated qualitatively by tracking Poincaré sections, and quantitatively by the variation coefficient as a function of axial position. Poincaré sections of tracers showed that KSM had the best mixing performance and RSM had two oval‐shaped segregated areas which periodically moved clockwise 90° in the cross‐sections of adjacent twisted tapes. Extensional efficiencies were computed radially and axially for all configurations. Both results showed that large dispersive mixing areas existed in the transition section. At the beginning of the first and end of the last element, the largest extensional efficiencies emerged, which were 1.07−1.21 times that at the transitions. The profiles of stretching rate showed that RSM tape had the weakest micro‐mixing ability, and the other three mixers had nearly identical stretching rates, much higher than RSM for Re < 10. With increasing Re, the mixing performance of MSM decreased first and then increased to be slightly higher than that of RSM. The secondary flows at transition regions were largely weakened for the different twist direction in the MSM. The respective roles of flow reversal and twist direction on mixing were evaluated with the stretching rates between static mixers and conventional stirred vessels.